Cambodia : 2009 Article IV Consultation-Staff Report; Staff Supplement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director. (IMF Staff Country Reports; Country Report ;, 2009)
This 2009 Article IV Consultation underlies that following a decade of high economic growth and significant poverty reduction, Cambodia's economy has been hard hit by the global crisis. Real GDP is contracting as key sectors falter-export and tourism receipts have fallen off sharply, reflecting a narrow production base, high concentration of exports, and softening external demand. In response to the slowdown, policies have been eased significantly. Executive Directors have emphasized the need to reduce the domestic financing component of the fiscal deficit while reprioritizing expenditure to protect vulnerable groups.